2021
DOI: 10.1177/0958305x211018453
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric impact of fiscal decentralization and environmental innovation on carbon emissions: Evidence from highly decentralized countries

Abstract: This study examines the asymmetric link between fiscal decentralization, environmental innovation, and carbon emissions in highly decentralized countries. Our preliminary findings strictly reject the preposition of data normality and highlight that the observed relationship is quantile-dependent, which may disclose misleading results in previous studies using linear methodologies. Therefore, a novel empirical estimation technique popularized as Method of Moments Quantile Regression is employed that simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(52 citation statements)
references
References 127 publications
(189 reference statements)
6
31
2
Order By: Relevance
“…In addition, a study conducted by Z. Khan, Ali, Umar, et al (2020), who examined the impact of environmental innovation and renewable energy on carbon emissions in G7 countries, suggested that future studies should also examine this area because the environment changes frequently, and different countries have different environmental and related factors. Similar results have been found in recent studies using eco‐innovation as a proxy for green innovation in different countries (He et al, 2021; Lingyan et al, 2021; Razzaq, Ajaz, et al, 2021; Razzaq, An, et al, 2021). Thus, to respond to this gap, the present study also examines the role of renewable energy and green innovation in environmental performance by examining the international trade of China.…”
Section: Introductionsupporting
confidence: 89%
“…In addition, a study conducted by Z. Khan, Ali, Umar, et al (2020), who examined the impact of environmental innovation and renewable energy on carbon emissions in G7 countries, suggested that future studies should also examine this area because the environment changes frequently, and different countries have different environmental and related factors. Similar results have been found in recent studies using eco‐innovation as a proxy for green innovation in different countries (He et al, 2021; Lingyan et al, 2021; Razzaq, Ajaz, et al, 2021; Razzaq, An, et al, 2021). Thus, to respond to this gap, the present study also examines the role of renewable energy and green innovation in environmental performance by examining the international trade of China.…”
Section: Introductionsupporting
confidence: 89%
“…Their primary findings suggest an inverted U shape relationship between FD and pollutants. Several other studies also documented the mixed effects of FD on environmental quality (Lingyan et al 2021; Khan et al 2021). The distinct outcome between decentralisation and ecological pollution is mainly explained via three main theories; (i) promotion, (ii) inhibition and (iii) no causality theory.…”
Section: Literature Reviewmentioning
confidence: 86%
“…This method is based on the relationships between population, income, technology and environmental effects, as presented in the following equation: normalIgoodbreak=normalPgoodbreak×normalAgoodbreak×normalT, where environmental pollution is denoted by I, population headcount represented by P, level of economic activity represented by A, and technology level defined by Dietz and Rosa (1997) and T. Dietz and Rosa (1994) generalised this basic model as a stochastic version, usually referred as STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) model. We have extended the same model following Lingyan et al (2021). CO2itgoodbreak=β1CFDitgoodbreak+β2GIitgoodbreak+β3INSitgoodbreak+β4GDPitgoodbreak+β5POPitgoodbreak+aigoodbreak+εit, where CO 2 , CFD, GI, INS, GDP, POP are carbon emissions, CFD index, green innovation, institutional governance index, population and per capita income, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second industrial revolution was driven by energy consumption around the world’s economic development, while the third industrial revolution also with technological innovation breakthroughs to enhance energy utilization ( Huang et al, 2022 ). Nevertheless, the long-term sloppy development model which sacrifices the environment has contributed to the global climate problem, which constrains the economic development of all nations nowadays, and especially has a significant impact on the living environment of humankind, threatening its prosperity and survival ( Yang et al, 2021a ; Lingyan et al, 2022 ). Because of the cross-regional nature of carbon emissions, high carbon emissions have emerged as a shared dilemma in the world ( Sharif et al, 2019 ; Rana et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%